Exploring the Post-COVID-19 Wellness Tourism Potential in Central Asia: A Case of Almaty Region, Kazakhstan - Sabirzhan, Saidullayev; Sheikhi, Ahmadreza; Anatolyevna, Abenova Yelena; Erikovna, Nurmukhanbetova Dinara; Namazbayeva, Zaure (Indonesian Journal of Geography, 2025)
This study examines the Almaty Region in southeast Kazakhstan as a potential wellness tourism destination and a regional hub for Central Asia. It primarily focuses on the perspectives of private-sector stakeholders, including entrepreneurs, owners, and administrators of wellness centers, while also exploring the demand for wellness tourism products (WTP) in the post-COVID-19 context. Additionally, the study highlights the region's natural wellness resources and their contribution to improving local quality of life, in line with Kazakhstan's Strategy 2030.  Data were collected through fieldwork, employing semi-structured face-to-face interviews and participant observation as the main methods. Over two months (March–April 2024), twelve in-depth interviews were conducted in Kazakh and Russian at wellness tourism centers catering to both domestic and international tourists. Observations were made at more than 30 centers near the hot springs of Sharyn village in the Almaty Region.  The findings indicate a growing interest in wellness services, positioning the Almaty Region as an emerging hub for wellness tourism in Central Asia. These results offer valuable insights for policymakers, investors, and tourism professionals aiming to develop wellness tourism in the area.Received: 2024-09-28  Revised: 2025-03-19  Accepted: 2025-08-15 Published: 2025-08-20